Polyolefin composite material as well as preparation method and application thereof
By using polyolefin composite materials such as regenerated polypropylene, linear low-density polyethylene, etc., combined with halogen-free flame retardant masterbatch and synergistic flame retardant, the problems of insufficient strength, toughness and flame retardant properties of the battery cover material are solved, and high-performance and environmentally friendly material preparation is achieved.
Patent Information
- Application Number
- CN202411977566.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing battery pack cover material cannot meet the strict requirements such as strength, toughness, flame retardant performance, and at the same time there are problems of waste of resources and difficulty in recycling.
Using a polyolefin composite material, which includes regenerated polypropylene, linear low-density polyethylene, toughener, halogen-free flame retardant masterbatch, compatible agent, synergistic flame retardant and anti-hydrolyzer, the material with excellent mechanical properties and flame retardant properties is prepared by melt-kneading and granulation through a twin-screw extruder.
It realizes the high strength, toughness and flame retardant properties of polyolefin composite materials, has good processing performance and environmental protection characteristics, and is suitable for applications such as battery pack covers.
Smart Images

Figure BDA0005220788610000021 
Figure BDA0005220788610000022 
Figure BDA0005220788610000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer composite materials, and in particular to a polyolefin composite material and a preparation method and application thereof. Background Art
[0002] In recent years, with the advancement of global energy transformation and carbon neutrality strategies, the energy storage battery industry has ushered in unprecedented development opportunities. As a key component of new energy vehicles and energy storage systems, the safety and reliability of energy storage battery packs are of vital importance. As an important part of the battery pack, the battery pack cover is responsible for protecting the battery module from external damage such as collision and extrusion.
[0003] At present, the commonly used materials for battery pack covers include metals, thermosetting plastics and carbon fiber composite materials. Among them, metal materials such as steel plates and aluminum alloys have high strength and rigidity, but they are dense and heavy, which does not conform to the development trend of lightweight vehicles; thermosetting plastics are light, but their flame retardancy and weather resistance still need to be improved, and it is difficult to achieve high-value recycling and reuse of products after they are scrapped; carbon fiber composite materials have the advantages of high strength, corrosion resistance, fatigue resistance and good flame retardancy, but the high cost limits their wide application.
[0004] Polypropylene (PP) is a semi-crystalline material that is non-toxic, odorless, low in density, has good overall performance, and is cost-effective. It is widely used in home appliances, automobiles, and other fields. However, the strength, toughness, and flame retardancy of existing polypropylene materials cannot meet the stringent requirements for battery pack covers. Summary of the invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a polyolefin composite material; the second purpose of the present invention is to provide a method for preparing the polyolefin composite material; the third purpose of the present invention is to provide an application of the polyolefin composite material.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a polyolefin composite material, comprising the following preparation raw materials: recycled polypropylene, linear low-density polyethylene, a toughening agent, a halogen-free flame retardant masterbatch, a compatibilizer, a synergistic flame retardant and an anti-hydrolysis agent;
[0008] The polymerizable monomers of the toughening agent include ethylene and propylene; and the particle size Dv50 of the halogen-free flame retardant masterbatch is ≥10 μm.
[0009] In some embodiments of the present invention, the polyolefin composite material further comprises the following preparation raw materials: an antioxidant and a lubricant.
[0010] In some embodiments of the present invention, the polyolefin composite material comprises the following raw materials, measured by mass percentage:
[0011]
[0012] In some specific embodiments of the present invention, the polyolefin composite material comprises the following preparation raw materials by mass percentage:
[0013]
[0014] In some embodiments of the present invention, the density of the recycled polypropylene is 0.89-0.93 g / cm 3 .
[0015] In some embodiments of the present invention, the melt index of the recycled polypropylene under the test condition of 230° C. / 2.16 kg is 1 g / 10 min-8 g / 10 min.
[0016] In some specific embodiments of the present invention, the melt index of the recycled polypropylene under the test condition of 230° C. / 2.16 kg is 1 g / 10 min-5 g / 10 min.
[0017] In the present invention, the recycled polypropylene is used as the resin matrix, which can give the composite material good processing characteristics and balanced physical and mechanical properties. Compared with the original polypropylene, the waste resources can be recycled, the cost is low, and it is more environmentally friendly.
[0018] In some embodiments of the present invention, the density of the linear low-density polyethylene is 0.91-0.93 g / cm 3 .
[0019] In some embodiments of the present invention, the linear low-density polyethylene has a melt index of 0.1 g / 10 min-10 g / 10 min under the test condition of 190° C. / 2.16 kg.
[0020] In some specific embodiments of the present invention, the linear low-density polyethylene has a melt index of 0.1 g / 10 min-3 g / 10 min under the test condition of 190° C. / 2.16 kg.
[0021] In the present invention, linear low-density polyethylene is used as a melt strength modifier, and the characteristics of polyethylene having a lower melting point and a wider melting range than polypropylene are fully utilized. During the blister molding process, the melt strength of polypropylene can be effectively improved, and the problems of blister cracking and severe wall thickness reduction caused by low melt strength can be avoided; and the linear low-density polyethylene also has a lower glass transition temperature and good flexibility, and can effectively improve the impact toughness of the composite material.
[0022] In some embodiments of the present invention, the content of ethylene monomer in the toughening agent is greater than or equal to 10 wt %.
[0023] In some embodiments of the present invention, the toughening agent has a melt index of 1 g / 10 min-10 g / 10 min under the test condition of 230° C. / 2.16 kg.
[0024] In some embodiments of the present invention, the toughening agent is selected from at least one of ethylene propylene diene monomer rubber (EPDM) and ethylene propylene copolymer (EPR).
[0025] In some specific embodiments of the present invention, the toughening agent is an ethylene-propylene copolymer.
[0026] In the present invention, a copolymer containing both ethylene segments and propylene segments is selected as a toughening agent, which can not only increase the toughness of the composite material and improve the bearing strength, but also improve the compatibility between recycled polypropylene and linear low-density polyethylene, overcome the delamination defects caused by thermodynamic incompatibility between the two, and improve the appearance characteristics of the composite material.
[0027] In some embodiments of the present invention, the phosphorus content in the halogen-free flame retardant masterbatch is 15wt%-30wt%, and the nitrogen content is 15wt%-35wt%.
[0028] In some embodiments of the present invention, the halogen-free flame retardant masterbatch uses polypropylene resin or polyethylene resin as a carrier.
[0029] In some embodiments of the present invention, the particle size Dv50 of the halogen-free flame retardant as an effective ingredient in the halogen-free flame retardant masterbatch is 5-15 μm.
[0030] In some embodiments of the present invention, the effective content of the halogen-free flame retardant masterbatch is 50 wt%-80 wt%.
[0031] In the present invention, nitrogen-phosphorus halogen-free flame retardant masterbatch is used. Compared with the same series of flame retardant powders, the halogen-free flame retardant masterbatch has a larger particle size, which can overcome the defects of poor fluidity and easy bridging of small particle powders, improve the dispersibility of the flame retardant in the mixing process, improve the mixing effect, and improve production efficiency.
[0032] In some embodiments of the present invention, the synergistic flame retardant is selected from at least one of kaolin, diatomaceous earth and wollastonite.
[0033] In some embodiments of the present invention, the average particle size of the synergistic flame retardant is 0.3-1.5 μm.
[0034] In some specific embodiments of the present invention, the synergistic flame retardant is kaolin.
[0035] In the present invention, inorganic flame retardants are used to exert a synergistic flame retardant effect. Their high heat capacity and low thermal conductivity are utilized to absorb heat and reduce the transfer of heat to combustible materials, thereby providing a heat shielding effect. The synergistic flame retardant decomposes and absorbs heat at high temperatures, thereby lowering the temperature of the material surface. The water vapor and carbon dioxide produced by the decomposition can also inhibit the spread of flames, thereby effectively improving the material's ablation resistance.
[0036] In some embodiments of the present invention, the compatibilizer includes a maleic anhydride grafted reactive compatibilizer.
[0037] In some embodiments of the present invention, the compatibilizer has a melt index of 60 g / 10 min-400 g / 10 min under the test condition of 190° C. / 2.16 kg.
[0038] In some embodiments of the present invention, the grafting rate of the compatibilizer is 0.3%-2%.
[0039] In some specific embodiments of the present invention, the compatibilizer is selected from at least one of maleic anhydride grafted polypropylene (PP-g-MAH), maleic anhydride grafted polyolefin elastomer (POE-g-MAH), and maleic anhydride grafted ethylene propylene diene monomer rubber (EPDM-g-MAH).
[0040] In the present invention, the addition of a compatibilizer can improve the interfacial bonding force between the halogen-free flame retardant masterbatch and the recycled polypropylene matrix resin, thereby effectively improving the strength and flame retardant properties of the material.
[0041] In some embodiments of the present invention, the melting point of the anti-hydrolysis agent is 105-120°C.
[0042] In some embodiments of the present invention, the anti-hydrolysis agent includes a polycarbodiimide anti-hydrolysis agent.
[0043] In the present invention, adding an anti-hydrolysis agent can effectively improve the defects of nitrogen-phosphorus halogen-free flame retardants, such as easy migration at high temperature and high humidity, inability to withstand high temperature boiling, and easy reduction of flame retardant performance, which is beneficial to ensuring the flame retardant performance of the material.
[0044] In some embodiments of the present invention, the antioxidant is selected from at least one of hindered phenol antioxidants, thioester antioxidants, and phosphite antioxidants.
[0045] In some embodiments of the present invention, the antioxidant is selected from at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester (antioxidant 1010), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanuric acid (antioxidant 3114), 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl) mesitylene (antioxidant 330), tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) isocyanurate (antioxidant 1790), trisnonylphenyl phosphite (antioxidant TNPP), tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168), and bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite (antioxidant 626).
[0046] In the present invention, the addition of an antioxidant can prevent the material from being oxidized and degraded at high temperature during processing, and at the same time improve the anti-oxidation and degradation performance of the material during use.
[0047] In some embodiments of the present invention, the lubricant is selected from at least one of zinc stearate, calcium stearate, magnesium stearate, polyethylene wax, polypropylene wax, and N,N'-ethylene bisstearamide.
[0048] In the present invention, the addition of lubricant can give the material good lubrication properties, improve the dispersion properties of the flame retardant and the synergistic flame retardant in the material, reduce the friction between the material and the equipment barrel, and improve the demoulding property and appearance gloss of the material.
[0049] The second aspect of the present invention provides a method for preparing the polyolefin composite material according to the first aspect of the present invention, comprising the following steps:
[0050] The prepared raw materials are mixed, melt-kneaded by a twin-screw extruder, and extruded into granules to obtain the polyolefin composite material.
[0051] In some embodiments of the present invention, the mixing is performed at a stirring speed of 1000-3000 r / min and the mixing time is 2-5 min.
[0052] In some embodiments of the present invention, the twin-screw extruder is a parallel twin-screw extruder with a length-to-diameter ratio of (35-45):1.
[0053] In some embodiments of the present invention, the temperatures of the feeding sections of the twin-screw extruder from the hopper to the die head are: first zone temperature: 120-180°C, second zone temperature: 130-180°C, third zone temperature: 170-190°C, fourth zone temperature: 170-200°C, fifth zone temperature: 170-200°C, sixth zone temperature: 170-200°C, seventh zone temperature: 170-200°C, eighth zone temperature: 170-200°C, ninth zone temperature: 190-210°C, tenth zone temperature: 190-220°C.
[0054] In some embodiments of the present invention, the screw speed of the twin-screw extruder is 300-700 r / min.
[0055] In some embodiments of the present invention, the frequency of the feeding screw of the main hopper of the twin-screw extruder is 20-45 Hz.
[0056] In some embodiments of the present invention, the vacuum degree of the twin-screw extruder is 400-600 mmHg.
[0057] The third aspect of the present invention provides the use of the polyolefin composite material described in the first aspect of the present invention in preparing a battery pack cover.
[0058] In some embodiments of the present invention, the battery pack includes an electric vehicle battery pack and an energy storage battery pack.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] 1) The polyolefin composite material provided by the present invention uses recycled polypropylene as the main matrix. Compared with virgin polypropylene, it can realize the recycling of waste resources and has the characteristics of economy, green environmental protection, low carbon and environmental friendliness; adding linear low-density polyethylene effectively improves the impact toughness and processing performance of the composite material; adding halogen-free flame retardant masterbatch, while ensuring the flame retardancy of the material, overcomes the defects of poor fluidity and easy powder bridging of the halogen-free flame retardant powder, and improves the production efficiency; adding a polymer toughening agent containing ethylene and propylene monomers improves the compatibility between the matrix resins, gives the material good appearance characteristics and improves the impact toughness; adding an anti-hydrolysis agent overcomes the defects of easy migration of nitrogen-phosphorus halogen-free flame retardants at high temperature and high humidity and not resistant to high temperature boiling, and improves the flame retardant performance of the material. Through the synergistic effect of multiple preparation raw materials, a tensile strength greater than 22MPa and a cantilever beam notched impact strength greater than 4.2KJ / m 2 , polyolefin composite materials with bending strength greater than 34MPa, bending modulus greater than 1500MPa, flame retardant grade up to V-0, high temperature ablation resistance and good processing performance;
[0061] 2) The preparation method of the polyolefin composite material provided by the present invention has simple steps and mild process conditions and is suitable for industrial use;
[0062] 3) The polyolefin composite material provided by the present invention has the characteristics of good mechanical properties, good flame retardancy, green and low carbon, resistance to high humidity environment, etc. Compared with the thermoplastic plastics currently commonly used for injection molding, the material is easy to extrude and can be formed by vacuum molding. It has the advantages of low molding and processing cost and high cost performance. It can be used in the preparation of plastic parts such as larger-sized battery pack covers and energy storage battery pack covers, and has good safety performance. DETAILED DESCRIPTION
[0063] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0064] The raw material information used in the following examples and comparative examples is shown in Table 1 below:
[0065] Table 1 Information of raw materials used in the examples and comparative examples
[0066]
[0067] Among them, the recycled polypropylene is 0.89-0.93g / cm 3 The melt index under the test conditions of 230℃ / 2.16kg is 2g / 10min-4g / 10min; the density of linear low-density polyethylene is 0.91-0.93g / cm 3 , the melt index under the test condition of 190℃ / 2.16kg is 0.7g / 10min-2.3g / 10min; the content of ethylene monomer in the ethylene-propylene copolymer is greater than or equal to 10wt%, and the melt index under the test condition of 230℃ / 2.16kg is 1g / 10min-10g / 10min; the grafting rate of the compatibilizer is 0.3%-2%, and the melt index under the test condition of 190℃ / 2.16kg is 60g / 10min-400g / 10min; the phosphorus content in the halogen-free flame retardant masterbatch is ≥18wt%, the nitrogen content is ≥19wt%, the effective content is 50wt%-80wt%, and the particle size Dv50 is 10μm; the average particle size of kaolin is 0.3-1.5μm; the melting point of the polycarbodiimide hydrolyzer is 105-120℃; the particle size Dv50 of the halogen-free flame retardant powder is 7.2μm.
[0068] Example 1
[0069] This example prepares a polyolefin composite material, and the raw materials are shown in Table 2:
[0070] Table 2 Composition of raw materials of polyolefin composite material in Example 1
[0071]
[0072] The preparation method of the polyolefin composite material comprises the following steps:
[0073] Add recycled polypropylene, linear low-density polyethylene, toughening agent, halogen-free flame retardant masterbatch, compatibilizer, synergistic flame retardant, anti-hydrolysis agent, antioxidant and lubricant into a high-speed mixer and stir at a speed of 1500 r / min for 5 minutes;
[0074] Add the uniformly stirred materials into the main feeding hopper of a parallel twin-screw extruder with a length-to-diameter ratio of 40:1, set the temperatures of each section (1st to 10th zones) of the extruder from the hopper to the die head to 150°C, 160°C, 170°C, 180°C, 180°C, 190°C, 180°C, 190°C, 190°C and 200°C, respectively, set the screw speed of the main machine to 450r / min, the frequency of the main hopper feeding screw to 28Hz, the vacuum degree to 500mmHg, and blend and melt extrude the materials;
[0075] The pellets coming out of the extruder die are cooled in a water tank, dried by a fan, and then enter a pelletizer for pelletizing to obtain a polyolefin composite material with a length of 3-5 mm and a diameter of 2-4 mm.
[0076] Example 2
[0077] This example prepares a polyolefin composite material, and the raw materials are shown in Table 3:
[0078] Table 3 Composition of raw materials of polyolefin composite material in Example 2
[0079]
[0080] The preparation method of the polyolefin composite material comprises the following steps:
[0081] Add recycled polypropylene, linear low-density polyethylene, toughening agent, halogen-free flame retardant masterbatch, compatibilizer, synergistic flame retardant, anti-hydrolysis agent, antioxidant and lubricant into a high-speed mixer and stir at a speed of 1500 r / min for 3 minutes;
[0082] Add the uniformly stirred materials into the main feeding hopper of a parallel twin-screw extruder with a length-to-diameter ratio of 40:1, set the temperatures of each section (1st to 10th zones) of the extruder from the hopper to the die head to 150°C, 160°C, 170°C, 180°C, 180°C, 190°C, 180°C, 190°C, 190°C and 200°C, respectively, set the screw speed of the main machine to 460r / min, the frequency of the main hopper feeding screw to 26Hz, the vacuum degree to 550mmHg, and blend and melt extrude the materials;
[0083] The pellets coming out of the extruder die are cooled in a water tank, dried by a fan, and then enter a pelletizer for pelletizing to obtain a polyolefin composite material with a length of 3-5 mm and a diameter of 2-4 mm.
[0084] Example 3
[0085] This example prepares a polyolefin composite material, and the raw materials are shown in Table 4:
[0086] Table 4 Composition of raw materials of polyolefin composite material in Example 3
[0087]
[0088]
[0089] The preparation method of the polyolefin composite material comprises the following steps:
[0090] Add recycled polypropylene, linear low-density polyethylene, toughening agent, halogen-free flame retardant masterbatch, compatibilizer, synergistic flame retardant, anti-hydrolysis agent, antioxidant and lubricant into a high-speed mixer and stir at a speed of 1800 r / min for 3 minutes;
[0091] Add the uniformly stirred materials into the main feeding hopper of a parallel twin-screw extruder with a length-to-diameter ratio of 40:1, set the temperatures of each section (1st to 10th zones) of the extruder from the hopper to the die head to 150°C, 160°C, 170°C, 180°C, 180°C, 190°C, 180°C, 190°C, 190°C and 200°C, respectively, set the screw speed of the main machine to 600r / min, the frequency of the main hopper feeding screw to 30Hz, the vacuum degree to 550mmHg, and blend and melt extrude the materials;
[0092] The pellets coming out of the extruder die are cooled in a water tank, dried by a fan, and then enter a pelletizer for pelletizing to obtain a polyolefin composite material with a length of 3-5 mm and a diameter of 2-4 mm.
[0093] Example 4
[0094] This example prepares a polyolefin composite material, and the raw materials are shown in Table 5:
[0095] Table 5 Composition of raw materials of polyolefin composite material in Example 4
[0096]
[0097]
[0098] The preparation method of the polyolefin composite material comprises the following steps:
[0099] Add recycled polypropylene, linear low-density polyethylene, toughening agent, halogen-free flame retardant masterbatch, compatibilizer, synergistic flame retardant, anti-hydrolysis agent, antioxidant and lubricant into a high-speed mixer and stir at a speed of 2000 r / min for 4 minutes;
[0100] Add the uniformly stirred materials into the main feeding hopper of a parallel twin-screw extruder with a length-to-diameter ratio of 40:1, set the temperatures of each section (1st to 10th zones) of the extruder from the hopper to the die head to 150°C, 160°C, 170°C, 180°C, 180°C, 190°C, 180°C, 190°C, 190°C and 200°C, respectively, set the screw speed of the main machine to 650r / min, the frequency of the main hopper feeding screw to 32Hz, the vacuum degree to 580mmHg, and blend and melt extrude the materials;
[0101] The pellets coming out of the extruder die are cooled in a water tank, dried by a fan, and then enter a pelletizer for pelletizing to obtain a polyolefin composite material with a length of 3-5 mm and a diameter of 2-4 mm.
[0102] Comparative Example 1
[0103] This comparative example prepares a polyolefin composite material, and the raw materials for preparation are shown in Table 6:
[0104] Table 6 Composition of raw materials of polyolefin composite materials in comparative example 1
[0105]
[0106] The preparation method of the polyolefin composite material comprises the following steps:
[0107] Add recycled polypropylene, linear low-density polyethylene, toughening agent, halogen-free flame retardant masterbatch, compatibilizer, synergistic flame retardant, anti-hydrolysis agent, antioxidant and lubricant into a high-speed mixer and stir at a speed of 2000 r / min for 4 minutes;
[0108] Add the uniformly stirred materials into the main feeding hopper of a parallel twin-screw extruder with a length-to-diameter ratio of 40:1, set the temperatures of each section (1st to 10th zones) of the extruder from the hopper to the die head to 150°C, 160°C, 170°C, 180°C, 180°C, 190°C, 180°C, 190°C, 190°C and 200°C, respectively, set the screw speed of the main machine to 650r / min, the frequency of the main hopper feeding screw to 32Hz, the vacuum degree to 580mmHg, and blend and melt extrude the materials;
[0109] The pellets coming out of the extruder die are cooled in a water tank, dried by a fan, and then enter a pelletizer for pelletizing to obtain a polyolefin composite material with a length of 3-5 mm and a diameter of 2-4 mm.
[0110] Comparative Example 2
[0111] This comparative example prepares a polyolefin composite material, and the raw materials for preparation are shown in Table 7:
[0112] Table 7 Composition of raw materials of polyolefin composite materials in comparative example 2
[0113]
[0114] The preparation method of the polyolefin composite material comprises the following steps:
[0115] Add recycled polypropylene, linear low-density polyethylene, toughening agent, halogen-free flame retardant masterbatch, compatibilizer, synergistic flame retardant, anti-hydrolysis agent, antioxidant and lubricant into a high-speed mixer and stir at a speed of 2000 r / min for 4 minutes;
[0116] Add the uniformly stirred materials into the main feeding hopper of a parallel twin-screw extruder with a length-to-diameter ratio of 40:1, set the temperatures of each section (1st to 10th zones) of the extruder from the hopper to the die head to 150°C, 160°C, 170°C, 180°C, 180°C, 190°C, 180°C, 190°C, 190°C and 200°C, respectively, set the screw speed of the main machine to 650r / min, the frequency of the main hopper feeding screw to 32Hz, the vacuum degree to 580mmHg, and blend and melt extrude the materials;
[0117] The pellets coming out of the extruder die are cooled in a water tank, dried by a fan, and then enter a pelletizer for pelletizing to obtain a polyolefin composite material with a length of 3-5 mm and a diameter of 2-4 mm.
[0118] Comparative Example 3
[0119] This comparative example prepares a polyolefin composite material, and the raw materials for preparation are shown in Table 8:
[0120] Table 8 Composition of raw materials of polyolefin composite materials in comparative example 3
[0121]
[0122]
[0123] The preparation method of the polyolefin composite material comprises the following steps:
[0124] Add recycled polypropylene, linear low-density polyethylene, toughening agent, halogen-free flame retardant powder, compatibilizer, synergistic flame retardant, anti-hydrolysis agent, antioxidant and lubricant into a high-speed mixer and stir at a speed of 2000 r / min for 4 minutes;
[0125] Add the uniformly stirred materials into the main feeding hopper of a parallel twin-screw extruder with a length-to-diameter ratio of 40:1, set the temperatures of each section (1st to 10th zones) of the extruder from the hopper to the die head to 150°C, 160°C, 170°C, 180°C, 180°C, 190°C, 180°C, 190°C, 190°C and 200°C, respectively, set the screw speed of the main machine to 650r / min, the frequency of the main hopper feeding screw to 32Hz, the vacuum degree to 580mmHg, and blend and melt extrude the materials;
[0126] The pellets coming out of the extruder die are cooled in a water tank, dried by a fan, and then enter a pelletizer for pelletizing to obtain a polyolefin composite material with a length of 3-5 mm and a diameter of 2-4 mm.
[0127] Comparative Example 4
[0128] This comparative example prepares a polyolefin composite material, and the raw materials for preparation are shown in Table 9:
[0129] Table 9 Composition of raw materials of polyolefin composite materials in comparative example 4
[0130]
[0131]
[0132] The preparation method of the polyolefin composite material comprises the following steps:
[0133] Add recycled polypropylene, linear low-density polyethylene, toughening agent, halogen-free flame retardant masterbatch, synergistic flame retardant, anti-hydrolysis agent, antioxidant and lubricant into a high-speed mixer and stir at a speed of 1500 r / min for 3 minutes;
[0134] Add the uniformly stirred materials into the main feeding hopper of a parallel twin-screw extruder with a length-to-diameter ratio of 40:1, set the temperatures of each section (1st to 10th zones) of the extruder from the hopper to the die head to 150°C, 160°C, 170°C, 180°C, 180°C, 190°C, 180°C, 190°C, 190°C and 200°C, respectively, set the screw speed of the main machine to 460r / min, the frequency of the main hopper feeding screw to 26Hz, the vacuum degree to 550mmHg, and blend and melt extrude the materials;
[0135] The pellets coming out of the extruder die are cooled in a water tank, dried by a fan, and then enter a pelletizer for pelletizing to obtain a polyolefin composite material with a length of 3-5 mm and a diameter of 2-4 mm.
[0136] Comparative Example 5
[0137] This comparative example prepares a polyolefin composite material, and the raw materials for preparation are shown in Table 10:
[0138] Table 10 Composition of raw materials of polyolefin composite material in comparative example 5
[0139]
[0140] The preparation method of the polyolefin composite material comprises the following steps:
[0141] Add recycled polypropylene, linear low-density polyethylene, toughening agent, halogen-free flame retardant masterbatch, compatibilizer, anti-hydrolysis agent, antioxidant and lubricant into a high-speed mixer and stir at a speed of 1500 r / min for 5 minutes;
[0142] Add the uniformly stirred materials into the main feeding hopper of a parallel twin-screw extruder with a length-to-diameter ratio of 40:1, set the temperatures of each section (1st to 10th zones) of the extruder from the hopper to the die head to 150°C, 160°C, 170°C, 180°C, 180°C, 190°C, 180°C, 190°C, 190°C and 200°C, respectively, set the screw speed of the main machine to 450r / min, the frequency of the main hopper feeding screw to 28Hz, the vacuum degree to 500mmHg, and blend and melt extrude the materials;
[0143] The pellets coming out of the extruder die are cooled in a water tank, dried by a fan, and then enter a pelletizer for pelletizing to obtain a polyolefin composite material with a length of 3-5 mm and a diameter of 2-4 mm.
[0144] Comparative Example 6
[0145] This comparative example prepares a polyolefin composite material, and the raw materials for preparation are shown in Table 11:
[0146] Table 11 Composition of raw materials of polyolefin composite material in comparative example 6
[0147]
[0148] The preparation method of the polyolefin composite material comprises the following steps:
[0149] Add recycled polypropylene, linear low-density polyethylene, toughening agent, halogen-free flame retardant masterbatch, compatibilizer, synergistic flame retardant, antioxidant and lubricant into a high-speed mixer and stir at a speed of 2000 r / min for 4 minutes;
[0150] Add the uniformly stirred materials into the main feeding hopper of a parallel twin-screw extruder with a length-to-diameter ratio of 40:1, set the temperatures of each section (1st to 10th zones) of the extruder from the hopper to the die head to 150°C, 160°C, 170°C, 180°C, 180°C, 190°C, 180°C, 190°C, 190°C and 200°C, respectively, set the screw speed of the main machine to 650r / min, the frequency of the main hopper feeding screw to 32Hz, the vacuum degree to 580mmHg, and blend and melt extrude the materials;
[0151] The pellets coming out of the extruder die are cooled in a water tank, dried by a fan, and then enter a pelletizer for pelletizing to obtain a polyolefin composite material with a length of 3-5 mm and a diameter of 2-4 mm.
[0152] Performance Testing
[0153] The polyolefin composite materials prepared in Examples 1-4 and Comparative Examples 1-6 were subjected to performance tests, and the test items and reference standards were as follows:
[0154] 1. Tensile strength: Tested in accordance with GB / T 1040-2018 "Determination of tensile properties of plastics";
[0155] 2. Izod notched impact strength: Tested in accordance with GB / T 1843-2008 "Standard for Determination of Izod Impact Strength of Plastics";
[0156] 3. Bending strength and bending modulus: refer to GB / T 9341-2008 "Determination of bending properties of plastics" for testing;
[0157] 4. Flame retardancy: Tested with reference to UL 94 fire rating;
[0158] 5. Ablation resistance time: The polyolefin composite materials in Examples 1-4 and Comparative Examples 1-6 were respectively used to prepare plastic square plates with a side length of 150 mm and a thickness of 3.0 mm, and placed above the blue inner flame of a Bunsen burner with a flame height of 125 mm and a blue inner flame height of 40 mm, 40 mm away from the Bunsen burner, and the plane of the sample was kept perpendicular to the flame. The time from the flame burning the center of the sample to the beginning of burning through was recorded, which was the ablation resistance time. Three plates were taken for each test and the average value was taken;
[0159] 6. Forming processability: Evaluation criteria are:
[0160] ①Excellent: During extrusion granulation, the feeding of raw and auxiliary materials is stable and smooth, the current of the extruder is stable, the drawing and pelletizing are normal; the vacuum forming is smooth, the surface of the product is flat, and it fits tightly with the mold;
[0161] ②Medium: The feeding of raw and auxiliary materials is unstable and not smooth during extrusion granulation, the current of the extruder fluctuates, the drawing and pelletizing are normal; the vacuum forming is smooth, the surface of the product is basically flat, and it fits tightly with the mold;
[0162] ③ Poor: The feeding of raw and auxiliary materials is unstable and not smooth during extrusion granulation, the current of the extruder fluctuates significantly, and the drawing and pelletizing are normal; the vacuum forming process is difficult, the surface of the product is uneven, and it does not fit tightly to the mold.
[0163] Table 12 Performance test results of polyolefin composite materials in Examples 1-4 and Comparative Examples 1-6
[0164]
[0165]
[0166] Table 12 shows the performance test results of the polyolefin composite materials in Examples 1-4 and Comparative Examples 1-6. It can be seen from Table 12 that the polyolefin composite materials prepared in Examples 1-4 have a tensile strength greater than 22 MPa and a notched cantilever beam impact strength greater than 4.2 KJ / m 2 The flexural strength is greater than 34MPa, the flexural modulus is greater than 1500MPa, the mechanical properties are balanced, and all are at a relatively good level; the flame retardant grade of the polyolefin composite material can reach V-0, with excellent flame retardant properties, good ablation resistance, and good processing performance, which can meet the requirements of the battery pack cover for the physical properties, flame retardant properties and processing performance of the preparation materials.
[0167] Compared with Example 4, after the linear low-density polyethylene is replaced by an equal amount of polyolefin elastomer POE, the strength and rigidity of the material decrease sharply. At the same time, the material is prone to apparent wrinkle defects during vacuum molding, and the molding stability of the material decreases; compared with Example 4, after the ethylene-propylene copolymer is replaced by an equal amount of polyolefin elastomer POE, the strength and rigidity of the material decrease; compared with Example 4, after the halogen-free flame retardant masterbatch is replaced by an equivalent halogen-free flame retardant powder, powder bridging occurs in the material during the production process, the processing performance of the material deteriorates, and the production efficiency decreases; compared with Example 2, when no compatibilizer is added, the strength of the material decreases significantly, but the rigidity of the material does not change much; compared with Example 1, when kaolin is not added, the high-temperature flame erosion resistance time of the material is shortened and the performance deteriorates; compared with Example 4, when no anti-hydrolysis agent is added, the mechanical properties of the material do not change much, but the flame retardant performance of the material in a warm water boiling environment decreases significantly. The polyolefin composite material provided by the present invention has synergistic effects among various components, so that the material has excellent mechanical properties, flame retardancy and molding processability. When the formula of the composite material is changed, the overall performance of the material will be reduced, which is not conducive to the application of the material.
Claims
1. A polyolefin composite material, characterized in that: The preparation method includes the following raw materials: recycled polypropylene, linear low-density polyethylene, toughening agent, halogen-free flame retardant masterbatch, compatibilizer, synergistic flame retardant and anti-hydrolysis agent; The polymerizable monomers of the toughening agent include ethylene and propylene; and the particle size Dv50 of the halogen-free flame retardant masterbatch is ≥10 μm.
2. The polyolefin composite material according to claim 1, characterized in that: The polyolefin composite material also includes the following preparation raw materials: antioxidant and lubricant.
3. The polyolefin composite material according to claim 2, characterized in that: The polyolefin composite material comprises the following raw materials by mass percentage:
4. The polyolefin composite material according to claim 3, characterized in that: The melt index of the recycled polypropylene under the test condition of 230°C / 2.16kg is 1g / 10min-8g / 10min; And / or, the linear low-density polyethylene has a melt index of 0.1 g / 10 min-10 g / 10 min under the test condition of 190° C. / 2.16 kg.
5. The polyolefin composite material according to claim 3, characterized in that: The content of ethylene monomer in the toughening agent is greater than or equal to 10 wt %; and / or the melt index of the toughening agent under the test condition of 230° C. / 2.16 kg is 1 g / 10 min-10 g / 10 min.
6. The polyolefin composite material according to claim 3, characterized in that: The phosphorus content in the halogen-free flame retardant masterbatch is 15wt%-30wt%, and the nitrogen content is 15wt%-35wt%; And / or, the synergistic flame retardant is selected from at least one of kaolin, diatomaceous earth and wollastonite.
7. The polyolefin composite material according to claim 3, characterized in that: The compatibilizer includes a maleic anhydride grafted reactive compatibilizer; And / or, the anti-hydrolysis agent includes a polycarbodiimide anti-hydrolysis agent.
8. The polyolefin composite material according to any one of claims 1 to 7, characterized in that: The polyolefin composite material has a diameter of 2-4 mm and a length of 3-5 mm.
9. The method for preparing the polyolefin composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The prepared raw materials are mixed, melt-kneaded by a twin-screw extruder, and extruded into granules to obtain the polyolefin composite material.
10. Use of the polyolefin composite material according to any one of claims 1 to 8 in preparing a battery pack upper cover.
Citation Information
Patent Citations
Halogen-free flame retardant thermoplastic wood-plastic composite material and preparation method thereof
CN104212192A
Halogen-free flame-retardant polyamide composite material with stable size and high glowing filament and preparation method of halogen-free flame-retardant polyamide composite material
CN113214642A
Polyolefin composite material as well as preparation method and application thereof
CN117801423A
Compatibilized polypropylene / polyethylene blend
KR102318208B1